In situ growth of a heterojunction CdS/TiO2 nanofiber monolithic photocatalyst sheet for enhanced hydrogen evolution. Issue 6 (15th February 2023) - Li, Wenbo; Zeng, Mingjun; Qi, Chunhong; Wang, Haifeng; Fan, Xuhui; Li, Xiaopeng; Xiao, Qi; Luo, Wei
Abstract : A heterojunction CdS/TiO2 nanofiber monolithic photocatalyst sheet was developed via facile in situ hydrothermal growth on Ti foil. The photocatalyst sheet can greatly enhance photocatalytic H2 production. Abstract : Herein, a heterojunction CdS/TiO2 nanofiber monolithic photocatalyst sheet is developed via facile hydrothermal in situ growth on a Ti foil. The CdS species are produced in the form of nanosheets embedded within and as thin layers coated on the intertwined TiO2 nanofibers, resulting in close CdS/TiO2 interfacial heterojunctions. The monolithic photocatalyst sheet shows significantly improved hydrogen evolution activity via a direct Z-scheme route.